PENDAMPINGAN UMKM KOPI PATI DALAM MENEMBUS PASAR EKSPOR MELALUI INOVASI PRODUK DAN STRATEGI PEMASARAN BERKELANJUTAN - Rohwiyati; Sulistya; Kim Budiwinarto; Juni Trisnowati; Dewi Pujiani (Surakarta Abdimas Journal, 2025)
This community service activity aims to enhance the capacity of coffee MSMEs in Pati Regency to meet the challenges of the global market, particularly in penetrating export channels. The main focus of the program is on mentoring product innovation and implementing sustainable marketing strategies aligned with international market demands. The implementation method includes need assessments, product innovation workshops (flavor diversification and packaging design), digital and sustainable marketing training, and export procedure simulations. The program employed a participatory approach through workshops, hands-on practices, and technical assistance. Evaluation was conducted using pre-test and post-test assessments as well as direct observation of participants’ implementation. The results showed a significant improvement in participants’ understanding (average increase of 68%) and their ability to develop new products and utilize digital platforms for promotion. This activity demonstrates that strategic collaboration and practical mentoring effectively equip MSMEs with the skills and confidence to compete in the export market.